Behavioral, Communication, and Service Experience Factors Influencing Consumers’ Intention to Use Call Center Services in Talk2Me Co., Ltd. - pongvipit, nutthamon; Supich, Apinya (Sripatum Review of Humanities and Social Sciences, 2026)
This study aims to (1) examine the level of factors influencing consumers’ intention to use call center services and (2) analyze the relationships and influences of user behavior, intercultural communication, customer satisfaction, and platform usage on consumers’ intention to use call center services. This research employed a quantitative approach. The sample consisted of 240 call center users of Talk2Me Co., Ltd., selected through simple random sampling. The research instrument was a questionnaire approved for human research ethics, demonstrating a high level of reliability. Data were analyzed using descriptive statistics, including mean and standard deviation, and inferential statistics, including Pearson’s correlation and multiple regression analysis, to examine relationships and causal influences among variables. The findings revealed that all four factors user behavior, intercultural communication, customer satisfaction, and platform usage had a statistically significant positive influence on consumers’ intention to use call center services at the .05 level. Among these, customer satisfaction had the strongest influence, followed by intercultural communication, user behavior, and platform usage, respectively. These four factors combined predict 68.2% of consumers’ intention to use call center services. The results highlight the importance of enhancing service experience and communication quality to strengthen consumers’ intention to use call center services and achieve a sustainable competitive advantage.